'Are We Still Running?': Violent Migration to Violent Refuge. Issue 1 (2nd January 2019) - John, Vaughn Mitchell
ABSTRACT: For most foreign nationals of African origin who lived in South Africa during 2008 and 2015, this period will be remembered with horror and fear. These were the years when South Africa's growing culture of xenophobia matured into mass deadly violence. This violence has been widely reported in the press and is the subject of much scholarly engagement. The pre-migration life stories of many who take refuge in South Africa are laden with violence but such narratives are less well known and reported. The forces at home that propel migration are frequently excessively violent and traumatic. Once in South Africa, many migrants experience further violence and vulnerability in their places of refuge, as in 2008 and 2015. The violence fuelling migration and characterising refuge are thus tragic combinations of multiple forms of physical, symbolic and structural violence. In identifying repeated cycles of trauma, dehumanisation and vulnerability, this article discusses the pleas of migrants for better understanding, formal recognition and support from South African citizens and the government. Finally, the role of peace education, including healing interventions, for creating greater justice and harmony between foreign nationals and their host communities is discussed.